The Effectiveness of Project-Based Learning in Enhancing Conceptual Understanding and Critical Thinking Skills: A Literature Analysis - Triyasa, Subuh; Yoto; Nurjanah, Nunung (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2025)
The demands of the Industrial Revolution 4.0 require graduates of Vocational High Schools (Sekolah Menengah Kejuruan/SMK) to possess strong conceptual understanding and well-developed critical thinking skills in order to address complex workplace problems. However, instructional practices in vocational education remain largely dominated by conventional approaches that are insufficient to foster higher-order thinking skills. This study aims to examine the effectiveness of Project-Based Learning (PjBL) in enhancing these two competencies through a systematic literature analysis of peer-reviewed scientific articles published between 2015 and 2024, guided by the PRISMA flowchart. The findings indicate that PjBL consistently contributes to improved learning outcomes; nevertheless, most existing studies tend to investigate conceptual understanding and critical thinking as separate constructs. The effectiveness of PjBL implementation is significantly influenced by external factors, including teacher readiness, infrastructure availability, and effective time management. This synthesis highlights the urgent need to integrate conceptual reinforcement and critical reasoning within project design in vocational high schools to better prepare competent graduates. Future research is recommended to employ mixed-methods approaches to examine the simultaneous relationship between these two competencies, thereby strengthening the empirical foundation of vocational education. Abstrak: Tuntutan Revolusi Industri 4.0 mengharuskan lulusan Sekolah Menengah Kejuruan (SMK) memiliki pemahaman konseptual yang kuat serta keterampilan berpikir kritis yang baik agar mampu menyelesaikan permasalahan kompleks di dunia kerja. Namun, praktik pembelajaran di pendidikan vokasi masih didominasi oleh pendekatan konvensional yang belum mampu secara optimal mengembangkan keterampilan berpikir tingkat tinggi. Penelitian ini bertujuan untuk mengkaji efektivitas penerapan Project-Based Learning (PjBL) dalam meningkatkan kedua kompetensi tersebut melalui analisis literatur sistematis terhadap artikel ilmiah bereputasi yang dipublikasikan pada periode 2015–2024 dengan menggunakan alur PRISMA. Hasil analisis menunjukkan bahwa PjBL secara konsisten berkontribusi terhadap peningkatan hasil belajar; namun demikian, sebagian besar penelitian masih mengkaji pemahaman konseptual dan keterampilan berpikir kritis secara terpisah. Keberhasilan implementasi PjBL sangat dipengaruhi oleh faktor eksternal, seperti kesiapan guru, ketersediaan infrastruktur, serta pengelolaan waktu yang efektif. Sintesis ini menegaskan urgensi integrasi penguatan konsep dan penalaran kritis dalam perancangan proyek di SMK guna menghasilkan lulusan yang kompeten. Penelitian selanjutnya direkomendasikan untuk menggunakan desain metode campuran (mixed methods) guna menguji hubungan simultan antara kedua variabel tersebut, sehingga dapat memperkuat landasan empiris pendidikan vokasi.